Use of polynucleotide/polyacrylamide-gel electrophoresis as a sensitive technique for the detection and comparison of ribonuclease activities. - Karpetsky, T P (1980)
A technique is described in which the incorporation of a polynucleotide substrate into the matrix of a polyacrylamide gel allows the use of electrophoresis for the detection of polycationic ribonuclease activity rather than simply the presence of protein. Because use is made of the catalytic properties of ribonucleases, polynucleotide/polyacrylamide-gel electrophoresis is apparoximately 10(5) times more sensitive for the detection of these enzymes than conventional gel electrophoresis with the use of protein-staining dyes. Initial studies showed that the poor migration, in the gels, of highly charged polycationic ribonucleases in the presence of negatively charged synthetic polynucleotides could be overcome by high concentrations of spermine. The positively charged polyamine, by neutralizing the polyanionic polynucleotide, enabled these basic enzymes to migrate considerable distances in the gel. Electrophoresis of the RNAases under conditions of low pH, and incubation of the gel at neutral pH followed by staining for polynucleotide, resulted in coloured gels containing clear bands that define regions of enzyme activity. Alterations in spermine concentration or substrate identity caused changes in the positions of these bands, suggesting a dynamic interaction among the enzyme, polyamine and polynucleotide. Because of the advantages, in terms of selectivity and sensitivity of polynucleotide/polyacrylamide-gel electrophoresis, this technique was used to demonstrate the nuclease homogenity of three purified bovine muscle enzymes, and to compare these enzymes with each other, as well as with bovine pancreatic ribonuclease A.